2012
DOI: 10.1213/ane.0b013e3182373887
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of an Injection Cephalad or Caudad to the Division of the Sciatic Nerve for Ultrasound-Guided Popliteal Block

Abstract: The caudad technique provided better surgical anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…A combined total of 176 patients were randomized to separate injections of the TN or CPN or a single pre-bifurcation injection around the common sciatic trunk. In one trial, separate injections yielded a higher rate of surgical anesthesia (96% vs 51%; p<0.001)205 while similar success rates (97%–100%) occurred in the other one 206. However, both studies found a shorter onset time for complete sensory blockade in the separate-injection group.…”
Section: Nerve Blocks Of the Sacral Plexusmentioning
confidence: 85%
“…A combined total of 176 patients were randomized to separate injections of the TN or CPN or a single pre-bifurcation injection around the common sciatic trunk. In one trial, separate injections yielded a higher rate of surgical anesthesia (96% vs 51%; p<0.001)205 while similar success rates (97%–100%) occurred in the other one 206. However, both studies found a shorter onset time for complete sensory blockade in the separate-injection group.…”
Section: Nerve Blocks Of the Sacral Plexusmentioning
confidence: 85%
“…No motor response to nerve stimulation was observed. The onset time for surgical block in the subparaneural group was shorter than in the extraneural group (respectively, median [range] values at 11 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] minutes and 17 minutes, for surgical block excluding the 6 failure patients), and sensory blockade of the tibial nerve lasted longer. With regard to the failure rate, the 6 patients presenting block failure (incomplete sensory blockade after 30 minutes) belonged to the extraneural group.…”
Section: Resultsmentioning
confidence: 99%
“…During the procedure, all patients received sedation via target-controlled infusion (propofol, Marsh model, concentration at the site of action 1.2 ng/mL). Ultrasound-guided lateral, short-axis, in-plane sciatic popliteal nerve blocks (linear array probe LA 435K, [8][9][10][11][12][13][14][15][16][17][18] MHz; Agile, Kontron Medical, France) were performed by anesthetists with more than 3 years' experience with ultrasoundguided blocks. The skin was prepared with an alcoholic povidoneiodine solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five RCTs directly compared USG with PNS (Table 2) for popliteal sciatic nerve block; 3 for single-injection techniques [44][45][46] and 2 for continuous popliteal sciatic nerve catheter placement. 47,48 Ten studies (Table 3) compared clinically relevant block-related outcomes based on different local anesthetic distribution patterns within these defined fascial compartments [49][50][51][52][53][54][55][56][57][58] : (1) circumferential local anesthetic distribution proximal versus distal with the sciatic nerve bifurcation (SNBF) and (2) subparaneural versus extraparaneural local anesthetic distribution proximal or distal with the SNBF. In addition, there were 2 RCTs that compared single-injection interfascial plane injection with targeted circumferential local anesthetic injection around the sciatic nerve at the anatomical level of the subgluteal space 59,60 and a single RCT that compared an ultrasound-guided subgluteal approach with an ultrasoundguided anterior approach.…”
Section: Sciatic Nerve Blockmentioning
confidence: 99%